Neoplatonic Love Logic in Feliciano de Silva's Amadis de Grecia (1530). - Crowley, Timothy D. (Intertexts)
The article presents a literary criticism of the book "Amadís de Grecia" by Feliciano de Silva. Topics discussed include the elements of Neoplatonic love logic in the book by de Silva, the 16th century Spanish literary genre of chivalric romances, and the literary motifs used by the author in the book. Also mentioned is the model of idealized love presented in secret marriage by the author.